Therapy-Related Late Adverse Events in Hodgkin's Lymphoma. (11th April 2013) - Gotti, Manuel; Fiaccadori, Valeria; Bono, Elisa; Landini, Benedetta; Varettoni, Marzia; Arcaini, Luca; Bonfichi, Maurizio
Abstract : Hodgkin's lymphoma (HL) is one of the most curable hematologic diseases with an overall response rate over 80%. However, despite this therapeutic efficacy, HL survivors show a higher morbidity and mortality than other people of the same age because of long-term therapy-related events. In the last decades, many efforts have been made to reduce these effects through the reduction of chemotherapy dose, the use of less toxic chemotherapeutic agents, and the introduction of new radiation techniques. In this paper, we will describe the main long-term effects related to chemotherapy and radiotherapy for HL, the efforts to reduce toxicity made in the last years, and the clinical aspects which have to be taken into consideration in the followup of these patients.